Improving Students’ Understanding and Explanation Skills Through the Use of a Knowledge Building Forum - Hamel, Christine; Turcotte, Sandrine; Laferrière, Thérèse; Bisson, Nicolas (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2015)
Education research has shown the importance of helping students develop comprenehsion skills. Explanation-seeking rather than fact-seeking pedagogies have been shown to warrant deeper student understanding. This study investigates the use of Knowledge Forum (KF) in K-6 classrooms (n = 251) to develop students’ explanation skills. To this end, we conducted pre- and post- activity interviews with students who used KF to investigate various topics. Their online collaborative discourse was also analyzed. Our results show that: 1) students’ explanations improved significantly between pre- and post-activity interviews, 2) active KF users scored higher than less active users on the post-activity interviews, and 3) students who had the best written explanations on KF scored much higher on the post-activity interviews even when they had scored much lower than less active students in the pre-activity interviews.